Popularity in Facebook Pages: What role network structural variables play? - Gutiérrez, Emiliano M.; Larrosa, Juan M.C. (AWARI, 2020)
Facebook pages (FP) are meeting points between events and actors in virtual social networks (RSV) of this platform. Companies and events bring together actors that participate through the online expression mechanisms that are enabled, through reactions, tagging, photo posting, liking, comments, etc. These interactions form online contact networks. We propose to investigate structural variables of the networks captured online with structural variables of these networks. We found that various structural variables related to concentration or disconnection between nodes are negatively associated with popularity measured by the number of likes, on the other hand, the most popular FPs associated with the media (radio and news).